The Improving Students' Science Process Skills through Implementing an Integrated Learning Model with Local Wisdom: Local wisdom for science leaarning - Husin, Vivi E. R; Lasmawan, I Wayan; Suharta, I Gusti Putu (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2024)
This research aims to determine the effectiveness of the integrated learning model of local wisdom in improving students' science process skills. This research uses a quasi-experimental design with two groups, namely an experimental group that applies an integrated learning model of local wisdom and a control group that applies a direct learning model. Data was collected using a science process skills test. The data obtained were analyzed using descriptive analysis and statistical analysis using MANOVA analysis. The results showed that there was a significant difference between the science process skills of students in the experimental group and the control group. This shows that the integrated learning model of local wisdom is effective in improving students' science process skills because there is a significant difference with an F value of 1.114.